Scoping Review of Technostress Drivers and Mitigation Strategies in Hybrid Work Environments - I Dewa Gede Sayang Adi Yadnya; Yeni Fajrin; Robby Fauji; Askolani Askolani; Eeng Ahman (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Objective: This study aims to systematically analyze the antecedents, impacts, and mitigation strategies of technostress specifically within the context of hybrid work environments. It seeks to address the emerging